THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) MODEL ON STUDENT LEARNING OUTCOMES IN INDONESIAN CULTURAL DIVERSITY MATERIAL CLASS IV SD NEGERI 1 PAGAR AIR - Sari, Intan; Nurmasyitah, Nurmasyitah; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2024)
Learning that only focuses on completing material and memorizing concepts makes students unable to develop their thinking patterns so that it has an impact on the learning outcomes obtained by students. Where the learning outcomes obtained by students do not reach the Learning Goal Achievement Criteria (KKTP). The formulation of the problem in this research is